Analisis Manajemen Olahraga Indonesia Beladiri Campuran Amatir - Mixed Martials Arts (IBCA MMA) Kediri - Nuzula, Haliza Firdausy; Rizky Maya Wulandari; Maharani Putri Wahyu Rahmawati; Hanifah Rosyidah Az Zahro; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the application of sports management functions at IBCA MMA Kediri using the POAC approach (planning, organizing, actuating, and controlling). This research employs a descriptive quantitative method, with data collection techniques through questionnaires distributed to 30 respondents consisting of athletes and coaches. The research instrument has passed validity and reliability tests, making it suitable for use. The results show that all aspects of management namely planning, organizing, actuating, and controlling are in the very good category. This indicates that the application of management functions at IBCA MMA Kediri has been running optimally in supporting the athlete development process. Thus, the sports organization management at IBCA MMA Kediri is considered effective, structured, and sustainable. This study is expected to serve as a reference for sports organizations in improving the quality of athlete management and development.